Nickel hydroxide nanoflower-based dispersive solid-phase extraction of copper from water matrix - Saylan, Meltem; Demirel, Rabia; Ayyildiz, Merve Firat; Chormey, Doste Selali; Cetin, Gulten; Bakirdere, Sezgin (SPRINGER, 2023)
In this work, a dispersive solid-phase extraction method based on Ni(OH)(2) nanoflowers (Ni(OH)(2)-NFs-DSPE) was developed to separate and preconcentrate copper ions from tap water samples for determination by flame atomic absorption spectrometry (FAAS). Ni(OH)(2)-NFs was synthesized using a homogeneous precipitation technique and used as sorbent for copper preconcentration. X-ray diffraction, scanning electron microscopy, and Fourier-transform infrared spectroscopy were used to characterize the synthesized sorbent. All experimental variables were carefully optimized to achieve a high enhancement factor of 107.5-folds with respect to the detection sensitivity of the conventional FAAS. The proposed method's analytical parameters including LOD, LOQ, and linear range were determined as 1.33 mu g/L, 4.42 mu g/L, and 3.0-40 mu g/L, respectively. To assess the applicability and reliability of the developed method, optimal conditions were applied to tap water samples and satisfactory percent recoveries (94-103%) were obtained for the samples spiked at 20 and 30 mu g/L. This validated the accuracy and feasibility of the developed method to real samples. The developed method can be described as a simple, efficient, and rapid analytical approach for the accurate determination of trace copper ions in water samples.
Keywords: Copper; Ni(OH)(2) nanoflowers; Dispersive solid-phase extraction; Flame atomic absorption spectrometry; Tap water; ATOMIC-ABSORPTION-SPECTROMETRY; ENVIRONMENTAL WATER; PRECONCENTRATION; SAMPLES; IONS; NANOPARTICLES; SEPARATION; LEAD(II); SORBENTS; CU(II); Environmental Sciences & Ecology